The potential of shoreline and shallow submerged Iron Age and Medieval archaeological sites in the Lofoten Islands, northern Norway - Wickler, Stephen (Archaeopress, 2013)
The Lofoten-Vesterålen archipelago (67°30’ - 69°30’N) is a chain of mountainous islands dissected by cirques, glacial valleys, and fjords that extends from northeast to southwest into the Norwegian Sea (Figure 1). Vesterålen is the northerly chain of islands and the seven islands of Lofoten lie to the south. The climate of Lofoten is mild despite this high latitude location. Temperatures are strongly affected by northward transport of heat through oceanic and atmospheric dynamics and the Norwegian Current flowing directly west of the islands carries warm water to the high latitudes of northern Norway (Hopkins 1991). Human habitation in this region has always been dependent on the marine environment with a reliance on the ocean and coastal areas for subsistence, shelter and transportation since initial settlement. Lofoten is situated in the midst of one of the most productive cod fishing grounds in the North Atlantic and the climate is also ideally suited for drying and preserving fish, another factor that helped this region develop as an important fishing center.